Kedudukan Hukum Anak Luar Kawin dalam Pemeliharaan Pasca Putusan Mahkamah Konstitusi No 46 /PUU–VIII /2010 - Cindi Amalia Putri; Rohman Kusmayadi, Rudy Catur (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The family is an essential social unit that contributes significantly to the protection of children's rights and welfare. In the context of Indonesian law, the legal status of children born out of wedlock was severely limited before the Constitutional Court Decision No. 46/PUU-VIII/2010. This study aims to examine changes in the legal status of out-of-wedlock children and their implications for custody after the decision. This research uses a qualitative method with a literature research approach, through the analysis of primary and secondary legal materials, such as Constitutional Court decisions, scientific literature, legal journals, and relevant laws and regulations. Prior to the Constitutional Court's ruling, children born out of wedlock were only recognized as having a civil relationship with their mother and mother's family, which had an impact on limited children's access to legal identity, custody, and inheritance. However, the Constitutional Court Decision No. 46/PUU-VIII/2010 opens up the opportunity to recognize the legal relationship between an out-of-wedlock child and his biological father, as long as it can be scientifically proven (through DNA tests) and legally. This change strengthens the position of children in obtaining custody (alimentasi), including the right to maintenance, protection, education, and financial support from the biological father. This ruling reflects significant progress in the protection of children's rights and the application of the principle of non-discrimination in Indonesian family law. Nevertheless, implementation in the field still faces challenges, both administratively, such as the convoluted recognition process, and socially, especially the stigma against children out of wedlock. Other challenges include low public legal literacy, limited access to scientific proof institutions, and the non-optimal role of the state in guaranteeing the rights of children born out of wedlock.